PAD, DAU, DAK, DBH, LUAS WILAYAH TERHADAP BELANJA MODAL DAN DAMPAKNYA PADA PERTUMBUHAN EKONOMI (Studi pada Provinsi/Wilayah Sumatera, Jawa, dan Bali Tahun 2012-2017) - Nadiah Dwi Retno; j Widiatmoko (Faculty of Economic and Business Universitas STIKUBANK, 2019)
This study examines the effect of PAD, DAU, DAK, DBH, Area on Capital Expenditures and their impact on Economic Growth. The population in this study is the Province / Region of Sumatra, Java, and Bali in 2012-2017.The sampling method uses purposive sampling with the study period from 2012-2017 producing 96 samples. The relationship and or influence between variables is explained by using the multiple regression analysis method. the results of the study show that PAD, DAK and area have a significant positive effect on Capital Expenditures, DAU and DBH have no effect on Capital Expenditures, Capital Expenditures have a significant negative effect on Economic Growth. Testing the control variable shows that the relationship between the Human Development Index has no effect on Economic Growth, while Direct Foreign Investment has a significant positive effect on Economic Growth. Keywords: Capital Expenditures, PAD, DAU, DAK, DBH, Area, Human Development Index, Direct Foreign Investment, and Economic Growth